A complex hyobranchial apparatus in a Cretaceous dinosaur and the antiquity of avian paraglossalia. (14th July 2015) - Hill, Robert V.; D'Emic, Michael D.; Bever, G. S.; Norell, Mark A.
Abstract : The highly specialized feeding apparatus of modern birds is characterized in part by paraglossalia, triangular bones or cartilages in the tongue that constitute part of the rarely fossilized hyobranchial apparatus. Here, we report on a new, juvenile specimen of the ankylosaurid dinosaur Pinacosaurus grangeri Gilmore, 1933 that provides the first evidence of paraglossalia outside of crown group Aves. The specimen is remarkable in preserving a well‐ossified hyobranchial apparatus, including paired paraglossalia, first and second ceratobranchials, epibranchials, and evidence of a median cartilaginous basihyal. Reassessment of Edmontonia, another ankylosaur, also reveals evidence of bony paraglossalia. Ankylosaur paraglossalia closely resemble those of birds, but are relatively larger and bear prominent muscle scars, supporting the hypothesis that ankylosaurs had fleshy, muscular tongues. The other hyobranchial elements, surprisingly, resemble those of terrestrially feeding salamanders. Ankylosaurs had reduced, slowly replacing teeth, as evidenced from dental histology, suggesting that they relied greatly on their tongues and hyobranchia for feeding. Some curved, rod‐like elements of other dinosaur hyobranchia are reinterpreted as second ceratobranchials, rather than first ceratobranchials as commonly construed. Ankylosaurs provide rare fossil evidence of deep homology in vertebrate branchial arches and expose severe biases against the preservation and collection of the hyobranchial apparatus. In light of these biases, we hypothesize that paraglossalia were present in the common ancestor of Dinosauria, indicating that some structures of the highly derived avian feeding apparatus were in place by the Triassic Period. © 2015 The Linnean Society of London